Integration of Financial Performance and Sharia Performance in Encouraging Financial System Stability and Economic Growth - Jairin Jairin (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2025)
This study aims to comprehensively analyze the relationship between Islamic bank performance, financial system stability, and economic growth within an integrative conceptual framework. This study uses a qualitative approach with a systematic literature review design of 10 DOAJ-indexed journal articles for the 2015–2025 period, as well as regulatory reports and relevant Islamic economics literature. The analysis was conducted through content analysis and thematic synthesis by grouping the findings into dimensions of financial performance (CAR, ROA, BOPO, NPF, FDR), sharia performance (financing model, risk sharing, maqashid-based performance), financial system stability, and contribution to economic growth. The results show that sound financial performance is a prerequisite for stability, while sharia characteristics such as real asset-based financing and risk distribution strengthen non-speculative stability. Maintained stability then creates a conducive intermediation space for real-sector-based economic growth. However, the resilience of Islamic banks is contextual and remains influenced by macroeconomic conditions and the quality of risk management. Theoretically, this study strengthens the multidimensional model of Islamic intermediation; In practice, these findings form the basis for formulating policies to strengthen capital, operational efficiency, and optimize productive financing to encourage inclusive and sustainable economic growth.